ANALISA MEKANISME PENGHITUNGAN, PEMOTONGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 PADA PT. BINA SWADAYA KONSULTAN TAHUN 2016 - Evi Margoretty Silalahi; Lucky Nugroho; Lawe Anasta (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2018)
ABSTRACT Income Tax Article (PPH) 21 tax on income in the form of salary, wages, honoraria, allowances, and other payments received or obtained by an individual domestic Taxpayer in respect of employment or occupation, services and activities. Therefore, government agencies and companies paying employees or employees are required to implement the calculation of Article 21 income tax on income received by their employees every month. This research was conducted at PT. Bina Swadaya Consultant. Furthermore, the purpose of this study was conducted to analyze the calculation and withholding of Article 21 Income Tax on employees of PT. Bina Swadaya Consultant, whether it has been in accordance with the Tax Law No.36 of 2008 on Income Tax. This research uses descriptive research method, and data collection technique used is documentation technique. The results of this study indicate that the calculation, deduction, deposit and reporting of PPh 21 applied by PT. Bina Swadaya Consultant is not in accordance with Law No.36 of 2008 on Income Tax article 4 paragraph 1, namely the calculation of Income Tax Article 21 Permanent Employees due to the company does not include attendance allowance in the calculation. Based on that, it is expected that the government through related parties can perform socialization and technical assistance in implementation of Article 21 PPH in enterprises in order to optimize state revenues. Key Words: Calculation of Income Tax (PPH) Article 21, Withholding of Income Tax Article 21   and Provision of Income Tax Article 21